Self-esteem levels, axiety levels, and coping strategies of physically handicapped adolescants - Tanjusay, Shiela Nova L.; Tuya, Christina T.; Tuya, Christina T.
This study was conducted to determine the self-esteem levels, anxiety levels, and coping strategies of physically handicapped adolescents.
Thesis (BA-Psychology-Management)--UP Visayas, Miag-ao, Iloilo
Keywords: Handicapped adolescents